2010
DOI: 10.1158/1055-9965.epi-09-0548
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Trial of a Psychosocial Telephone Counseling Intervention inBRCA1 andBRCA2 Mutation Carriers

Abstract: Background: Responses following BRCA1/2 genetic testing are relevant for the comprehension of risk status and may play a role in risk management decision making. The objective of this study was to evaluate a psychosocial telephone counseling (PTC) intervention delivered to BRCA1/2 mutation carriers following standard genetic counseling (SGC). We examined the effect of the intervention on distress and the concerns related to genetic testing.Methods: This prospective randomized clinical trial included 90 BRCA1/2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 34 publications
2
34
0
Order By: Relevance
“…This particular confusion stresses the need for clear definition and language when discussing SDM, which has been attempted in a prior publication from this group (Cohen et al 2012). We suspect that the use of telephone GC as a primary SDM may be lower than reported here, however recent literature is demonstrating increased use and acceptance of telephone genetic counseling (Bradbury et al 2011;Doughty Rice et al 2010;Graves et al 2010;Shanley et al 2007;Sutphen et al 2010).…”
Section: Discussionmentioning
confidence: 70%
“…This particular confusion stresses the need for clear definition and language when discussing SDM, which has been attempted in a prior publication from this group (Cohen et al 2012). We suspect that the use of telephone GC as a primary SDM may be lower than reported here, however recent literature is demonstrating increased use and acceptance of telephone genetic counseling (Bradbury et al 2011;Doughty Rice et al 2010;Graves et al 2010;Shanley et al 2007;Sutphen et al 2010).…”
Section: Discussionmentioning
confidence: 70%
“…One program included written materials on emotional responses to genetic testing, making medical decisions, managing family concerns, and coping with stress in addition to 5 weekly telephone counseling sessions delivered by master's-level mental health counselors. 128 Groups represent another option, and it has been demonstrated that supportive-expressive therapy groups can relieve feelings of isolation and improve psychosocial functioning, cancer worries, and depression in individuals with BRCA1/ BRCA2 mutations. 129 Finally, providing partner support and facilitating family communication regarding hereditary cancer has been recommended, because studies have demonstrated that family members may also experience distress throughout the genetic testing process.…”
Section: Discussionmentioning
confidence: 99%
“…Other intervention outcomes include improving understanding of cancer genetics during counseling [37,[39][40][41][42][43][44][45][46]; enhancing carriers' well-being after testing [23,[47][48][49][50]; and supporting them during disclosure of genetic test results [51][52][53][54]. Genetic information was delivered with an information booklet [29], a CD-ROM [25,29,38], a phone call [42,48], a computer-based program [25,27], and with peer-educators [54]. Modes of delivery included a one-day retreat to provide updated information [50], a short follow-up session [46], pre-counseling materials [34,38,43], virtual reality technology [44], and phone counseling for psychological support to carriers and their sisters [42,48].…”
Section: Introductionmentioning
confidence: 99%
“…Genetic information was delivered with an information booklet [29], a CD-ROM [25,29,38], a phone call [42,48], a computer-based program [25,27], and with peer-educators [54]. Modes of delivery included a one-day retreat to provide updated information [50], a short follow-up session [46], pre-counseling materials [34,38,43], virtual reality technology [44], and phone counseling for psychological support to carriers and their sisters [42,48]. Outcomes included satisfaction with the intervention, knowledge improvement, intention to use genetic testing, and reducing emotional burden.…”
Section: Introductionmentioning
confidence: 99%